Case report of Ureaplasma urealyticum meningitis in a patient with thymoma and hypogammaglobulinaemia - Ting Zhang (BMC, 2021)
Abstract Background Ureaplasma urealyticum (UU) is found among the normal vaginal flora in a considerable proportion of asymptomatic women; however, adult central nervous system (CNS) infection of UU is extremely rare. Good's syndrome (GS) is an adult-onset immunodeficiency characterized by thymoma, hypogammaglobulinaemia, low or absent B‑cells, and an inverted CD4+/CD8+ T‑cell ratio. Patients with GS usually have severe or recurrent infections. Case presentation We describe the case report of a 49-year-old woman who developed UU meningitis. Initial routine anti-viral and anti-bacterial therapy showed no improvement in the patient's condition. Next-generation sequencing (NGS) of cerebrospinal fluid (CSF) identified the UU DNA sequence. Accordingly, a diagnosis of UU meningitis was made, and minocycline therapy was initiated. The patient responded favourably, with no signs of disease at subsequent follow-up. According to the severity and rarity of the case, secondary immunodeficiency was suspected. Flow cytometry found hypogammaglobulinaemia. Combined with the previous history of thymoma, the patient was diagnosed with immune deficiency disease of GS. Conclusions This case may be the first adult case report in the literature describing UU meningitis in a patient with GS. The diagnosis of GS should be considered in patients presenting with unexplained antibody deficiency and thymoma.